(untitled) (International Journal of Mathematics and Physics, 2026)
Abstract. Urban air pollution poses a serious threat to public health, particularly in areas with heavy traffic, such as street canyons. This paper numerically investigates the effect of noise barriers of varying heights (0.1H, 0.2H, 0.3H, where H is the building height) on the dispersion of a passive pollutant (ethylene) in a street canyon model. The simulation is based on the Reynolds-averaged Navier-Stokes (RANS) equations and the SST k-ω turbulent model. The numerical model is verified by comparison with published experimental data and large eddy simulation (LES) results. Spatiotemporal distributions of pollutant concentrations are analyzed. The results show that a barrier of medium height (0.2H) forms a stable recirculation zone, acting as a "trap" for pollutants with maximum concentrations. A low barrier (0.1H) has a negligible effect, while a high barrier (0.3H) effectively screens the leeward zone but promotes pollutant accumulation on the windward side. A conclusion is drawn about the dual effect of barriers and the need to consider aerodynamic effects in their design. Keywords: computational fluid dynamics (CFD), air pollution, street canyon, noise barrier, pollutant dispersion, RANS, SST k-ω.